Analysis of Food Inflation in Indonesia using the Nonlinear Autoregressive Distributed Lag Approach - Salsabila, Nur; Rahkmawati, Yeni; Muslim, Agus; Rahman, Mizan Ikhlasul (JTAM (Jurnal Teori dan Aplikasi Matematika), 2026)
Food Inflation remains one of the most persistent sources of price volatility in Indonesia and poses a significant challenge for macroeconomic stability and household welfare. This study conducts quantitative empirical time series research to examine the asymmetric effects of Money Supply (M2) and Farmers Terms of Trade (FTT) on Food Inflation. The analysis uses monthly data from 2011 to 2023 obtained from Bank Indonesia and Statistics Indonesia and applies the Nonlinear Autoregressive Distributed Lag (NARDL) model, which is appropriate for capturing asymmetry and accommodating variables integrated at different orders. The selection of M2 is based on monetary theory which states that changes in liquidity influence aggregate demand and inflation, while the use of FTT is supported by agricultural and development literature showing that farmers purchasing power affects food production capacity and food price dynamics. The results reveal significant asymmetric effects in both the short and long run. Increases and decreases in M2 both raise Food Inflation, and the stronger effect during declining M2 reflects downward price rigidity and the dominance of quasi money in Indonesia. A decline in FTT significantly increases long run inflation through constraints on agricultural input access and reduced food supply. The findings also confirm inflation persistence. These results imply that liquidity management and policies that strengthen farmer purchasing power are essential to stabilize food prices. The study recommends integrating monetary policy with agricultural support measures to mitigate future food inflation pressures.